Groundwater Modelling of Leachate Plume by Using MODFLOW at Simpang Renggam Landfill - Sa’at, Nur Liyana Syahira; Tajul Baharuddin, Mohammad Faizal (Progress in Engineering Application and Technology, 2021)
Landfilling method cause a major threat to groundwater resources. Simpang Renggam dumpsite was in a bad condition because overflow of leachate from a landfill during heavy rainfall and was in process to be closed due to reach the maximum capacity. This research study is to evaluate the potential of contamination risk due to leachate leakage at the landfill by using visual MODFLOW. The objective of this studies is to identify the groundwater contamination risk due to potential leachate leakage and seepage beneath the municipal landfill. The groundwater cannot be detected directly if they were polluted due to their condition underneath surface. However, using MODFLOW, the seepage of leachate from CEP Landfill was identified and able to detect the affected area surrounding groundwater resources in Simpang Renggam. The leachate flow movement was obtained and reach the surface water source that located at the low-lying area. Thus, this study shows that software of MODFLOW can be used for solving the same problem involved and can avoid other catchment area for being affected due to any other source of pollutants.